The relations and adaptational problems of male homosexuals / Eleanor M. Ong Mei Lin - Eleanor M. Ong , Mei Lin (1985)
This graduation exercise is a study to investigate if the male homosexuals in our society experience problems due to their sexuality and their adaptation to the situations. Before that, I will attempt to gauge the attitude of the society towards homosexuality to see if it is the societal reactions that gives birth to the male homosexuals ' problems. The problems of the male homosexuals will be seen in selected aspects which are social, economical, political and sexual. The first chapter opens with the aim, scope and theoretical framework of this research. The first chapter opens with The methodology and problems experienced during fieldwork will also be included. Chapter two relates the essential understanding of homosexuality and the theoretical factors causing it. An analysis of the societal reactions towards homosexuality will be in the main of chapter three, while chapters four and five is the analysis of the male homosexual respondents ' relationships with people in the previously selected aspects. The conclusion is to be found in chapter six.